The status of Elk during the Mesolithic - Bridault, Anne (HAL CCSD, 1992)
International audience The distribution of elk (Alces alces) remains during the Mesolithic period suggests a genuine geographical disparity in elk population densities. Several kinds of explanations are presented, involving the mode of acquisition of the remains (hunting or exchange of elk products) and the possible symbolic status of elk.